Self-induced global rotation of chiral and other mechanical metamaterials. (15th May 2020) - Dudek, Krzysztof K.; Gatt, Ruben; Wojciechowski, Krzysztof W.; Grima, Joseph N.
Highlights: Different mechanical metamaterials can exhibit a self-induced global rotation. The extent of the global rotation can be controlled via mass distribution. Chiral systems may manifest a superior extent of the global rotation. Metamaterials with a discrete mass distribution may induce their own global rotation. Abstract: In this work, through the use of Molecular Dynamics simulations, we show the capability of different mechanical metamaterials to induce their own global rotational motion as a result of an internal deformation. We also show that one of the considered structures, i.e. the hexachiral system, may manifest a superior extent of the global rotation in comparison to other systems. In addition to that, we discuss that the self-induced global rotation can be observed for mechanical metamaterials with a discrete mass distribution which allows to prove that this phenomenon is not limited to macroscopic systems and applications involving the control of the rotational motion of objects such as satellites or wind turbines where the continuous mass distribution of structural elements is normally required. In fact, this study serves as a blueprint to show that a similar effect may also be expected for various systems at very different scales.